Effectiveness and safety of obeticholic acid in a Southern European multicentre cohort of patients with primary biliary cholangitis and suboptimal response to ursodeoxycholic acid. Issue 4 (12th December 2020) - Gomez, Elena; Garcia Buey, Luisa; Molina, Esther; Casado, Marta; Conde, Isabel; Berenguer, Marina; Jorquera, Francisco; Simón, Miguel‐Angel; Olveira, Antonio; Hernández‐Guerra, Manuel; Mesquita, Monica; Presa, Jose; et al.
Summary: Background: Obeticholic acid (OCA) was recently approved as the only on‐label alternative for patients with primary biliary cholangitis (PBC) with intolerance or suboptimal response to ursodeoxycholic acid (UDCA). However, few data are available outside clinical trials. Aim: To assess the effectiveness and safety of OCA in a real‐world cohort of patients with non‐effective UDCA therapy. Methods: Open‐label, prospective, real‐world, multicentre study, enrolling consecutive patients who did not meet Paris II criteria, from 18 institutions in Spain and Portugal. Effectiveness was assessed by the changes in GLOBE and UK‐PBC scores from baseline. POISE and Paris II criteria were evaluated after 12 months of OCA . Liver fibrosis was evaluated by FIB‐4 and AST to platelet ratio index (APRI). Results: One hundred and twenty patients were eligible, median time since PBC diagnosis 9.3 (4.0‐13.8) years, 21.7% had cirrhosis, and 26.7% received had previous or concomitant treatment with fibrates. Seventy‐eight patients completed at least 1 year of OCA. The Globe‐PBC score decreased to 0.17 (95% CI 0.05 to 0.28; P  = 0.005) and the UK‐PBC score decreased to 0.81 (95% CI −0.19 to 1.80; P  = 0.11). There was a significant decrease in alkaline phosphatase of 81.3 U/L (95% CI 42.5 to 120; P  < 0.001), ALT 22.1 U/L (95% CI 10.4 to 33.8; P  < 0.001) and bilirubin 0.12 mg/dL (95% CI 0 to 0.24; P  = 0.044). FIB‐4 and APRI remained stable. According to the POISE criteria, 29.5% (23 out of 78) achieved response. The adverse events rate was 35%; 11.67% discontinued (8.3% due to pruritus). Conclusions: This study supports data from phase III trials with significant improvement of PBC‐Globe continuous prognostic marker score among OCA‐treated patients with good tolerability.